Amalan pengajaran inkuiri guru kimia melalui interaksi verbal di sekolah menengah - Sim, Winnie Siew Li (2014)
Inquiry teaching is one of the important approaches in teaching chemistry. This study focuses on inquiry teaching practices through verbal interaction to provide detailed information on inquiry teaching practices among chemistry teachers. This study investigates the practices of inquiry teaching based on teachers’ questions, teachers’ statements, students’ questions, students’ statements and silence or confusion through verbal interaction. Besides that, verbal interaction at macroscopic, submicroscopic and symbolic levels, teaching sequence, teaching pattern and teacher’s role were also investigated. This study is a combination of quantitative and qualitative approach involving 23 chemistry teachers of secondary schools in Kuala Lumpur. The triangulation technique was used includes questionnaire, observation, semi-structured interview and document evidence. Inquiry Teaching Verbal Interaction Observation Instrument which consists of 50 categories was used in this study. This instrument was modified based on existing classroom observation instruments. A total of ninety two classroom observations were audio and video recorded for data analysis purposes. Descriptive statistics and cluster analysis were used to determine the frequency, percentage and pattern of inquiry teaching practices of chemistry teachers. Findings showed that statements made by teachers dominated other verbal interactions, either in theory or practical chemistry classes. Verbal interaction at multiple representation levels focused more on macroscopic level and it was found that there was less integration at these levels. The dominant teaching sequence was teacher’s question followed by students’ response and ended with teacher’s evaluation. Cluster analysis showed that there were three teaching patterns in theory and practical classes. The majority of respondents practiced teacher-centered approach in the theory classes but used a combination of teacher-centered and student-centered approaches in the practical classes. Teachers acted as information providers as compared to inquirers. Based on the findings, the implementation of inquiry teaching approach was found to be not in line with the aims of inquiry teaching. Therefore, a Model Inquiry Teaching Based on Verbal Interaction was proposed. Verbal interaction guideline was also suggested for chemistry teachers to implement inquiry approach effectively.